Impact of the direct transfer to percutaneous coronary intervention-capable hospitals on survival to hospital discharge for patients with out-of-hospital cardiac arrest. (April 2018) - Cournoyer, Alexis; Notebaert, Éric; de Montigny, Luc; Ross, Dave; Cossette, Sylvie; Londei-Leduc, Luc; Iseppon, Massimiliano; Lamarche, Yoan; Sokoloff, Catalina; Potter, Brian J.; Vadeboncoeur, Alain; Larose, Dominic; et al.
Abstract: Aims: Patients suffering from out-of-hospital cardiac arrest (OHCA) are frequently transported to the closest hospital. Percutaneous coronary intervention (PCI) is often indicated following OHCA. This study's primary objective was to determine the association between being transported to a PCI-capable hospital and survival to discharge for patients with OHCA. The additional delay to hospital arrival which could offset a potential increase in survival associated with being transported to a PCI-capable center was also evaluated. Methods: This study used a registry of OHCA in Montreal, Canada. Adult patients transported to a hospital following a non-traumatic OHCA were included. Hospitals were dichotomized based on whether PCI was available on-site or not. The effect of hospital type on survival to discharge was assessed using a multivariable logistic regression. The added prehospital delay which could offset the increase in survival associated with being transported to a PCI-capable center was calculated using that regression. Results: A total of 4922 patients were included, of whom 2389 (48%) were transported to a PCI-capable hospital and 2533 (52%) to a non-PCI-capable hospital. There was an association between being transported to a PCI-capable center and survival to discharge (adjusted odds ratio = 1.60 [95% confidence interval 1.25–2.05], p < .001). Increasing the delay from call to hospital arrival by 14.0 min would offset the potential benefit of being transported to a PCI-capable center. Conclusions: It could be advantageous to redirect patients suffering from OHCA patients to PCI-capable centers if the resulting expected delay is of less than 14 min.